(untitled) (Window of Nursing Journal, 2025)
One of the efforts to improve the performance and professionalism of nurses in accordance with their field of work through increasing the competence of individual nurses is by establishing a professional career ladder system for nurses. This study aims to describe the perception of clinical nursing career paths. This study uses a descriptive research design. Sampling of 64 nurses using simple random sampling with a perception questionnaire instrument about the career path of nurses. The data analysis technique used is univariate analysis with the results of an overview or description of the frequency distribution and the percentage of each variable examined. The results of this study indicate that the description of nurses’ perceptions of career paths on several indicators, namely promotions obtained by more than half of the nurses having a good perception of 49 people (76.6%), then awards were obtained by more than half of the nurses having a good perception of 47 people (73 .4%), then the recognition was obtained that more than half of the nurses had a good perception of 45 people (70.3%), then career development was obtained by 39 people (60.9%), and the indicator with a good perception of frequency and the lowest percentage was career challenges it was obtained that more than half of the nurses had a good perception of 36 0 people (56.3%). Perceptions of nurse career paths at the Ibnu Sina Main Teaching Hospital UMI showed that nurses chose more positive statements, so it can be concluded that the perceptions of nurse career paths were mostly in the good category. It is hoped that the results of this study can be used as reference material for those who wish to conduct further research.